2004
DOI: 10.1046/j.1365-2982.2003.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural regulation of tone in the oesophageal body: in vivo barostat assessment of volume–pressure relationships in the feline oesophagus

Abstract: Recent combined manometric-barostat studies demonstrated that the oesophageal body exhibits both peristaltic contractions and tone. This study further characterized the neural modulation of tone in the feline oesophageal body. Simultaneous oesophageal barostat and manometry were performed in 20 adult cats under ketamine sedation. Oesophageal tone and peristalsis were assessed in the distal smooth muscle oesophagus. Cholinergic modulation was studied using neostigmine, erythromycin, atropine and vagotomy. Nitre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…To the best of our knowledge, this is the first description of esophageal tone changes, measured with a barostat, during acute esophagitis. This technique has been used to assess esophageal tone in normal animals (17,30) and healthy human volunteers (18). Cholinergic excitatory input seems to be the main control mechanism (30).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first description of esophageal tone changes, measured with a barostat, during acute esophagitis. This technique has been used to assess esophageal tone in normal animals (17,30) and healthy human volunteers (18). Cholinergic excitatory input seems to be the main control mechanism (30).…”
Section: Discussionmentioning
confidence: 99%
“…A dose of 0.1 ml/kg of suspension ‘A’ or ‘B’ was administered directly into the oral cavity of each dog, using a syringe, every 12 hours for two weeks, by a member of our research group who was unaware of the treatment protocol. The dogs allocated in the treatment group therefore received 1 mg/kg sildenafil every 12 hours; this dose was chosen on the basis of previous studies in humans and cats (Bortolotti and others 2000, Zhang and others 2004), in which the same dose was effective in relaxing the LOS. In order to obtain a prolonged effect on LOS tone, the drug was administered twice daily, since the half-life of sildenafil in dogs is about five hours (Walker and others 1999).…”
Section: Methodsmentioning
confidence: 99%
“…In cats under ketamine sedation, it was suggested that tonic contractile activity in the esophageal body is mainly caused by a continuous cholinergic excitatory input, and a NO inhibitory mechanism may have a complementary role in the tonic regulation (Zhang et al, 2004). According to Beyak et al (2000), intravenous injections of L-NA reduced the number of oropharyngeal swallows and the induction of primary peristalsis in the smooth muscle portion but not in the striated muscle portion, whereas administration of L-NA into the fourth ventricle in the brain reduced the swallows and peristalsis in both smooth and striated muscles.…”
Section: A Esophagusmentioning
confidence: 99%